The relationship between motivation and achievement motivation among players in the Algerian National Professional Football Championship - MEGAG, Kamel (sports creativity, 2025)
Sports psychologists have been interested in studying the subject of motivation, which is part of the scientific knowledge of the nature of human behavior and reaching formulas to modify and direct it, or at least to predict it in certain circumstances and situations. In this study, we tried to find out the relationship between motivation and achievement motivation among players of the Algerian National Professional Football Championship.